Recommending Interesting Activity-Related Local Entities - Tang, Jie; White, Ryen W.; Bailey, Peter (34th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2011), Beijing, China, 2011)
When searching for entities with a strong local character (e.g., a museum), people may also be interested in discovering proximal activity-related entities (e.g., a café). Geographical proximity is a necessary, but not sufficient, qualifier for recommending other entities such that they are related in a useful manner (e.g., interest in a fish market does not imply interest in nearby bookshops, but interest in other produce stores is more likely). We describe and evaluate methods to identify such activity-related local entities.